Selective catalytic reduction of nitric oxide by methane in the presence of oxygen over CaO catalyst - Fliatoura, K. D.; Verykios, Xenophon E.; Costa, Costas; Efstathiou, A. M. (My University, 1999)
The selective catalytic reduction of nitric oxide by methane in the presence of oxygen was studied over CaO catalyst in the temperature range 550–850°C. The nitric oxide conversion-versus-temperature profile was found to depend on oxygen feed concentration, while the selectivity to N2formation was found to be 100% and independent of oxygen feed concentration in the range 1–10 mol%. The kinetic study has shown that the reaction order with respect to NO and CH4is 1.0 and 0.5, respectively. On the other hand, the reaction order with respect to O2was found to be slightly positive for O2feed concentrations up to 1 mol% and slightly negative at higher concentrations. The apparent activation energy of the reaction in the presence of oxygen was found to be 14.6 kcal/mol. The addition of 2.5 mol% CO2and 5 mol% H2O in the feed stream had a considerable inhibiting effect on NO conversion in the range 550–650°C, while a small inhibiting effect of CO2and a positive effect of H2O were observed in the range 700–850°C. Temperature-programmed desorption (TPD) of NO revealed the presence of two well-resolved NO peaks in the temperature range 250–650°C, a behavior also observed during a temperature-programmed oxidation experiment under O2/He flow. However, during temperature-programmed surface reaction under CH4/He flow the NO desorption spectrum showed a significant shift of the stronger adsorbed NO species toward lower temperatures. Preadsorbed CO2on the CaO surface was found to largely affect the chemisorption of NO and its desorption kinetics during TPD. The amount of deposited carbon-containing species on the catalyst surface during reaction was determined with transient titration experiments and it was found to be small.
Keywords: Calcium oxide; Methane; Nitric oxide reduction by CH4; Nitric oxide reduction kinetics; Nitrogen oxides; NO reduction by hydrocarbon